OR08-04 Differences in Advanced Lipoprotein Profile Between Rabson-Mendenhall Syndrome and Lipodystrophy - Al-Jundi, Mohammad (J Endocr Soc, 2020)
Insulin resistance (IR) is associated with metabolic dyslipidemia (high triglycerides [TG] and low HDL) and increased cardiovascular disease (CVD) risk. In obesity-associated IR, dyslipidemia is thought to be caused by increased insulin-mediated stimulation of hepatic lipogenesis, whereas IR in glucoregulatory pathways leads to hyperglycemia. This dichotomy in insulin signaling pathways is termed selective insulin resistance. Rare human conditions exist in which there is extreme, non-selective, IR impairing all insulin signaling pathways (e.g. mutations of the insulin receptor, INSR) or extreme IR affecting only selected intracellular insulin signaling pathways analogous to obesity (e.g. lipodystrophy). Lipodystrophy leads to very high TG, low HDL, and increased CVD, while INSR mutation leads to low TG and high HDL, with unknown CVD risk. We sought to further characterize the lipid phenotype and atherogenicity in these conditions in order to understand effects of different insulin signaling pathways on CVD risk. We studied 7 patients with INSR mutation (42% female; 5 homozygous; 2 heterozygous) and 21 with lipodystrophy (85% female; 5 generalized; 16 partial). Fasting lipoprotein profiles were assessed by NMR using the LP4 deconvolution algorithm. The major lipoprotein particle categories defined by this method are small, medium, and large HDL and LDL particles (HDLP and LDLP) and very small, small, medium, large, and very large TG rich lipoprotein particles (TRLP). Very small TRLP (median 189.6 [68.7, 315.0] vs 4.5 [0.00, 9.4], p=0.0001), small LDLP (mean 1425.0 ± 636.2 vs 612.8 ± 233.9, p=0.003), small HDLP (mean 14.0 ± 4.7 vs 9.0 ± 3.2, p=0.014) were more elevated in patients with lipodystrophy vs INSR mutation. This lipoprotein profile has been associated with increased atherosclerotic coronary artery disease. GlycA, a marker of inflammation was also more elevated in lipodystrophy vs INSR mutation (435.9 ± 107.2 vs 315.7 ± 74.4, p=0.01). Insulin resistance assessed by HOMA-IR was higher in patients with INSR mutation vs lipodystrophy (mean 93.5 ± 94.4 vs 15.6 ± 14.7, p=0. 00085).) Lipoprotein insulin resistance (LPIR), an index of IR based on lipoprotein particles, was lower in patients with INSR mutation (25.0 ± 19.0 vs 84.0 ± 9.0, p < 0.0001) despite their higher HOMA-IR. In conclusion, severe, selective insulin resistance in patients with lipodystrophy was associated with a more atherogenic lipoprotein particle profile and increased inflammation compared to severe, non-selective insulin resistance caused by INSR mutations. Patients with INSR mutations had a striking discrepancy between a glucose/insulin-based index of insulin resistance (HOMA-IR) and a lipid-based marker of insulin resistance (LPIR). These findings point toward a key role of selective insulin resistance in the development of an atherogenic lipid profile, which should lead to increased CVD risk.